2015
DOI: 10.1007/s11605-014-2631-0
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Resection Induces Long-Term Changes in the Enteric Microbiota of Mice

Abstract: Purpose The enteric microbiome is known to play a major role in healthy gut homeostasis and several disease states. It may also contribute to both the intestinal recovery and complications that occur in patients with short bowel syndrome. The extent and nature of alterations to the gut microbiota following intestinal resection, however, are not well studied in a controlled setting. The purpose of this investigation is to characterize the effects of massive small bowel resection on the murine enteric microflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
1
29
1
Order By: Relevance
“…This contrasts with an earlier study in which we revealed significant alterations in the microbiota of the small bowel, but not in the feces after SBR 9 . The variations between current and prior studies might be due to altered time of fecal collection (7 and 90 days versus 21 days), small bowel lumen versus passed stool, or different housing conditions from one time of year to another.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts with an earlier study in which we revealed significant alterations in the microbiota of the small bowel, but not in the feces after SBR 9 . The variations between current and prior studies might be due to altered time of fecal collection (7 and 90 days versus 21 days), small bowel lumen versus passed stool, or different housing conditions from one time of year to another.…”
Section: Discussioncontrasting
confidence: 99%
“…7 Increased abundance of Firmicutes (primarily Gram-positive bacteria) is one of the more prevalent findings involving an obese phenotype 8 . Similar to obesity, we have identified a remarkably similar pattern of increased Firmicutes abundance in the small intestine after SBR 9 . Using our murine SBR model, we have established that mice exhibit a unique body composition profile in which fat is preferentially replaced over lean muscle during recovery.…”
supporting
confidence: 66%
“…Vancomycin is not absorbed from the gastrointestinal tract and kills Gram-positive bacteria, which have been described to bloom in the gut of mice after SBR(35) and patients(21, 36) with short gut syndrome. Taken together, the observations of our past and present studies would endorse critical roles for both Gram-negative and positive organisms working synergistically to promote resection-associated steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of small bowel resection, changes in the ileal microbial community were observed up to 90 days after surgery [157]. The intestinal microbiota may influence anastomotic leak after gastrointestinal surgery.…”
Section: Gut Microbiota and Surgery For Gastrointestinal Tract Cancersmentioning
confidence: 99%